AGR358: Land Survey / Faculty of Plantation and Agrotechnology - UiTM, Faculty of Plantation and Agrotechnology (2018)
Introductory course of land surveying, to expose student to the knowledge and skills in land surveying, in conducting simple land surveying in the estate, to draw and read map and to estimate areas and volumes of earthwork.